Local government management development in Scotland: a study of public policy and its implementation, 1967-2002 - Mackie, Robert (2004)
This study examines the public policy on management development in Scottish local government from 1967 to 2002. Public policy literature tends to reflect the public administration context of its heyday in the 1970s and early 1980s. The focus then was on improving policy formulation to take account of potential implementation problems and thus to counter the failures due to bad policy identified in the multiplicity of real case studies. This study focuses on the public policy area of management development provision for local government managers taking into account recent developments in the post-devolution period. - Reproduced.
Keywords: Government policy - Scotland; Local government - Scotland; Local government